1994
DOI: 10.3109/09286589409071443
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of referral routes and diagnostic accuracy in cases of suspected glaucoma

Abstract: Over a nine-month period two hundred and thirteen referrals to the Department of Ophthalmology of the Leicester Royal Infirmary, England, for suspicion of glaucoma were examined by a single ophthalmologist. Ninety-nine percent of referrals resulted from the findings at an optometric visit. Despite this, less than 32% were confirmed as having glaucoma and less than 23% had ocular hypertension. Twenty-nine percent showed no abnormality. Of those with glaucoma 19% showed advanced field loss in their worse eye. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
58
3

Year Published

2003
2003
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(64 citation statements)
references
References 10 publications
3
58
3
Order By: Relevance
“…9,10 A previous study has shown that 90% of patients with glaucoma are referred to the hospitals on the basis of abnormal findings by optometrists. 26 Most people would require change of spectacles or reading glasses from about the age of 40 years, which incidentally is also about the age glaucoma incidence appears significant. In the UK, the optometrist plays an important role in glaucoma detection, while in Ghana there are only few optometrists and their role in glaucoma referrals at the present time is fairly limited.In both Korle-Bu Teaching and Trust Hospitals referrals are usually from mass screening exercises by ophthalmic nurses providing outreach services or attached to other hospitals and clinics where there are no ophthalmologists, and also employers for routine medical examination.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 A previous study has shown that 90% of patients with glaucoma are referred to the hospitals on the basis of abnormal findings by optometrists. 26 Most people would require change of spectacles or reading glasses from about the age of 40 years, which incidentally is also about the age glaucoma incidence appears significant. In the UK, the optometrist plays an important role in glaucoma detection, while in Ghana there are only few optometrists and their role in glaucoma referrals at the present time is fairly limited.In both Korle-Bu Teaching and Trust Hospitals referrals are usually from mass screening exercises by ophthalmic nurses providing outreach services or attached to other hospitals and clinics where there are no ophthalmologists, and also employers for routine medical examination.…”
Section: Discussionmentioning
confidence: 99%
“…There is no formal screening programme for glaucoma in the UK, so detection is largely dependent on the public attending an optometrist for sight testing, with optometrists responsible for over 90% of referrals to the Hospital Eye Service. [5][6][7][8] Three tests/examinations are recommended for the detection of glaucoma; measurement of IOP, visual field and optic disc assessment. However, optometrist case-finding and referral criteria vary considerably across the profession.…”
mentioning
confidence: 99%
“…11 Recent studies have reported positive predictive values (PPV) of optometrist referrals for glaucoma ranging between 0.31 and 0.50. 5,7,9,[11][12][13][14] As PPV is directly related to prevalence and prevalence is low, this figure implies that optometrist referrals have a high degree of specificity. 15 The proportion of undetected glaucoma in the developed world, however, remains at about 50%.…”
mentioning
confidence: 99%
“…Between 10-33% of glaucoma patients present with advanced glaucoma, [1][2][3][4][5][6] this is a risk factor for blindness. 3,5,[7][8][9] Reduction in intraocular pressure is the only treatable risk factor for glaucoma and may be achieved by either medical or surgical intervention.…”
Section: Introductionmentioning
confidence: 99%